2015
DOI: 10.1175/jcli-d-15-0004.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Sudden Stratospheric Warming Definitions in Reanalysis Data*

Abstract: Sudden stratospheric warmings (SSWs) are characterized by a pronounced increase of the stratospheric polar temperature during the winter season. Different definitions have been used in the literature to diagnose the occurrence of SSWs, yielding discrepancies in the detected events. The aim of this paper is to compare the SSW climatologies obtained by different methods using reanalysis data. The occurrences of Northern Hemisphere SSWs during the extended-winter season and the 1958–2014 period have been identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 38 publications
2
55
0
Order By: Relevance
“…La Nina winters identified by Free and Seidel (2009) and Butler and Polvani (2011 Nishii et al (2011) and Taguchi (2016), using the same Japanese reanalysis. Differences across reanalyses on SSW detection are already documented (Charlton and Polvani 2007;Palmeiro et al 2015) and do not alter our results (not shown). The QBO phase is evaluated using the 5°S-5°N average zonal mean zonal wind at 50 hPa, which is close to the most favorable level to find the link with the NH identified by Baldwin and Dunkerton (1998).…”
Section: A Event Detectionsupporting
confidence: 73%
“…La Nina winters identified by Free and Seidel (2009) and Butler and Polvani (2011 Nishii et al (2011) and Taguchi (2016), using the same Japanese reanalysis. Differences across reanalyses on SSW detection are already documented (Charlton and Polvani 2007;Palmeiro et al 2015) and do not alter our results (not shown). The QBO phase is evaluated using the 5°S-5°N average zonal mean zonal wind at 50 hPa, which is close to the most favorable level to find the link with the NH identified by Baldwin and Dunkerton (1998).…”
Section: A Event Detectionsupporting
confidence: 73%
“…The light‐ice composite has a higher rate of SSW events (7 out of 9) than the heavy‐ice composite does (9 out of 17); thus, the stratospheric influence is stronger. However, it is difficult from observations to see if the higher rate results from lower sea‐ice conditions or from decadal variability of SSW events (e.g., winters in the 1980s and after 2000 had more frequent SSW events than those in the 1990s; Palmeiro et al, ). Furthermore, the rates of SSW to WPV depend on SSW definitions.…”
Section: Resultsmentioning
confidence: 99%
“…When we linearly detrend the BKS sea‐ice time series, the heavy‐ice composite consists of winters in the middle period (i.e., the 1990s in which only a few SSWs occurred), whereas the light‐ice composite consists of winters mostly in early and recent periods (i.e., the 1980s and years after 2005 in which SSWs frequently occurred). Consequently, the simple detrending approach for the full period may emphasize the decadal behavior of SSW events (Palmeiro et al, ). Since the shorter period does not suffer from such strong decadal behavior (Figure c), we will add our analysis on the shorter period for checking the robustness of the results and discuss the alternative approach only briefly.…”
Section: Methodsmentioning
confidence: 99%
“…We detect SSWs from December to March, leading to a mean frequency of 5.9 SSWs per decade, in accordance with most other studies (Butler et al, ; Charlton et al, ; Palmeiro et al, ). We are not including November as we consider conditions up to 90 days before any particular SSW and want to minimize the number of summer days included in our analysis.…”
Section: Methodsmentioning
confidence: 99%